Algorithm for predicting threshold retinopathy of prematurity is insufficient and fundus examinations are still needed before 31 weeks. (10th December 2018) - Wirth, M; Naud, A; Caputo, G; Hascoët, J M
Abstract: Aim: We evaluated the weight, insulin‐like growth factor‐1, neonatal, retinopathy of prematurity (WINROP) algorithm for very premature infants. Method: Infants born before 32 weeks who had undergone fundus examinations in the neonatal intensive care unit at the University Hospital of Nancy were included in this French retrospective cohort study from July 2012 to July 2016. We evaluated how well the WINROP software predicted threshold retinopathy of prematurity (ROP). Results: We studied 570 infants with a mean gestational age of 28.7 ± 1.8 weeks and a mean birth weight of 1110 ± 297 g: 28.1% had ROP and 1.2% had threshold ROP. The overall WINROP sensitivity was 57.1%, specificity was 46.0%, predictive positive value was 1.3% and predictive negative value was 98.9%. At more than 30 weeks of gestation or 1250 g, these figures rose to a respective specificity of 100% and 95.7% and respective predictive negative value of 100% and 100%. There were independent associations between the severity of ROP and the Apgar score at five minutes, the duration of oxygen therapy and non‐invasive ventilation. Conclusion: WINROP worked better on preterm infants born from 31 weeks onwards or weighing over 1250 g. Fundus examinations remain necessary for infants born earlier or lighter.